How Access to Credit Facilities Affects Youth Participation in Agro- Pastoralism in Mandera County, Kenya - Ibrahim, Issak Gababa; Mutunga, Stephen Laititi; Koome, Martin (International Journal of Professional Practice, 2024)
Credit facilities drive economic development in most sectors of the economy. However, due to the uncertainty of weather and other risks, agricultural sector has been disadvantaged in terms of access to credit. Access to credit, particularly by youth who lack a steady source of income is even more challenging since they are considered high risk borrowers by financial institutions. This study sought to establish factors that influence access to credit by youth in Mandera County. The study adopted a descriptive survey research design, and as was guided by Push and Pull theory. The target population was 2900 youth registered in youth groups in Mandera County. A sample size of 351respondents was obtained from the 145 registered youth groups through purposive sampling technique. Structured questionnaires were distributed to the respondents through drop and pick method were used to collect data. The questionnaire was tested for face and content validity during piloting in the neighboring county of Wajir. Reliability was assessed and a Cronbach alpha coefficient of 0.77 was realized. Results were analyzed using descriptive and inferential statistics. Regression analysis was carried out and results for F-tests and Analysis of Variance (ANOVA) at a 95% confidence generated. The null hypothesis for credit access was rejected (β=0.273, P=0.000)). This meant that lack of credit access had a significant effect on youth engagement in agro pastoralism. Further, a positive and significant correlation between credit access by youth (or lack of it) and their engagement in agro pastoralism was reported (r=0. 541, p=0.000). It was concluded that credit access was critical to adoption of agro pastoralism by youth in Mandera County. The study recommended that the county government of Mandera creates an enabling environment to encourage more participation of youth in agro pastoralism, and to work out modalities of easing restrictions to credit access.